Analisis Automation, Keamanan, dan Kecepatan Jaringan 5G dalam Implementasi Internet of Things (IoT) - Yani, Achmad; Irfansyah, Dicki; Kurniawan, Sigit; Muhidin, Muhidin (Journal of Mathematics and Technology (MATECH), 2024)
The development of 5G technology presents great potential in the implementation of the Internet of Things (IoT) by increasing communication speed, data security, and process automation. This article analyzes the role of 5G networks in supporting the IoT ecosystem with a descriptive qualitative approach. The main focus of this study is how aspects of automation, security, and speed in 5G networks contribute to the efficiency and effectiveness of IoT systems in various industrial sectors. The results of the study show that 5G networks not only provide low latency and high throughput, but also face complex security challenges, which require innovative mitigation strategies. This study provides recommendations for the development of more resilient systems in dealing with cyber threats and optimizing IoT networks.